Analisis Penerapan Pengelolaan Dana Desa - Diah Dewi Nawang Wulan; Herlina Helmy (Jurnal Eksplorasi Akuntansi, 2023)
The purpose of this study was to find out how the accountability of village fund management which includes planning, implementation, administration, reporting and accountability in Sari Mulya and Kuamang Villages, Jambi Province. The research method used is an interpretive qualitative research method. Data sources have primary and secondary data. Data collection techniques were carried out by observation, interviews, and documentation. The survey results show that: (1) Although planning applies the principles of participation and transparency, the preparation of village fund plans and village budgets has not been in accordance with the time specified in the Minister of Home Affairs Regulation Number 20 of 2018 Article 43 (2) The implementation of village funds has not implemented the principle of transparency and participation and accountability. the village government has implemented the principle of accountability related to income and expenditure in accordance with Permendagri Number 20 of 2018 concerning Village Finance Article 63 (3) The village government applies the principle of accountability in accordance with Permendagri Number 20 of 2018 concerning Village Finance. at the administrative stage (4) Reporting and accountability applies the principles of accountability and transparency, but reporting and accountability. The implementation of the APBD is not in accordance with the stipulated time limit and is not in line with Permendagri Number 20 of 2018.